Macrophage migration inhibitory factor-794 CATT microsatellite polymorphism and risk of tuberculosis: a meta-analysis. Issue 4 (6th July 2018) - Ma, Mingbiao; Tao, Lvyan; Liu, Aihua; Liang, Zhang; Yang, Jiaru; Peng, Yun; Dai, Xiting; Bai, Ruolan; Ji, Zhenhua; Jian, Miaomiao; Bao, Fukai
Abstract : Tuberculosis (TB) is a chronic infectious disease that has been threatening public health for many years. Several studies have shown the relationship between the macrophage migration inhibitory factor (MIF)-794 CATT (MIF-794 CATT) microsatellite polymorphism and susceptibility to TB. However, the results remain inconclusive. Therefore, we aim to find out the impact of MIF-794 CATT microsatellite polymorphism on risk of TB by a comprehensive meta-analysis. We conducted a systematic study search in PubMed, Embase, the Cochrane Library, and the China National Knowledge Infrastructure (CNKI) up to October 2017. Five studies involving 836 cases and 678 controls were included in the current meta-analysis. We calculated the pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) to estimate the association between the MIF-794 CATT microsatellite polymorphism and risk of TB. The reliability of the results were evaluated with trial sequential analysis (TSA). The results suggested that the MIF-794 CATT microsatellite polymorphism was significantly associated with the susceptibility of TB in all comparisons for allele (7 + 8 compared with 5 + 6, OR = 1.56, 95% CI = 1.31–1.87, P <0.00001) and genotype (7/X + 8/X compared with 5/X + 6/X, OR = 1.81, 95% CI = 1.39–2.36, P <0.0001). Therefore, the meta-analysis indicated the MIF-794 allele CATT7 and CATT8 may be a risk factor to increase the susceptibility of TB, which was confirmed by TSA.